Prevalence of antibodies to prothrombin in solid phase (aPT) and to phosphatidylserine-prothrombin complex (aPS/PT) in patients with and without lupus anticoagulant - Bertolaccini, Maria Laura; Sciascia, Savino; Murru, Veronica; Garcia-Fernandez, Cesar; Sanna, Giovanni; Khamashta, Munther A. (Thrombosis and Haemostasis, 2013)
Antibodies to prothrombin in solid phase (aPT) and those to phosphatidiyserine- prothrombin complex (aPS/PT) have been suggested to strongly correlate with the presence of lupus anticoagulant (LA). As their clinical diagnostic value and true relationship with the LA remains elusive, we designed this study to evaluate the prevalence and significance of aPT and aPS/PT in a large cohort of patients with and without LA. Samples from 257 patients were included. aPT and aPS/PT were tested by ELISA. LA was tested as per the current criteria from the ISTH Subcommittee on LA-Phospholipid-dependent antibodies. aPS/PT and aPT were found in 51% and 32% of LA-positive (LA+ve) patients and in 22% and 28% of LA-negative (LA-ve) patients, respectively. Thrombosis, particularly venous thrombosis was associated with IgG aPT in the LA+ve group (p=0.0006) and in the LA-ve group (p=0.017). Antibodies to phosphatidylserine-prothrombin, either IgG and IgM were associated with thrombosis in general (p=0.0003) in particularly with venous thrombosis in the LA+ve group (p<0.0001 for IgG and p=0.025 for IgM; respectively) and the LA-ve group (p=0.028, 0.02 and 0.001, respectively). Further multivariate logistic regression analysis showed that LA and of IgG and/or IgM aPS/PT were independent risk factors for thrombosis and pregnancy loss. In conclusion, aPS/PT, but not aPT, are more frequently found in patients with LA. Their association with thrombosis seems to be independent of the presence of LA.
Keywords: Prothrombin; phosphatidylserine-prothrombin complex; lupus anticoagulant; antiphospholipid syndrome